Письмо Иштар-Шуму-Эреша - Асархаддону (abl 519 = las 13) в контексте прогнозирования внешней и внутренней политики Ассирии - Святополк-Четвертынский, Игорь Анатольевич (Институт языкознания РАН)
Дана попытка показать политическую и военную деятельность ассирийского царя Асархаддона во взаимодействии с аналитической астрологией на примере письма Иштар-шуму-эреша – Асархаддону (ABL 519 = LAS 13 = SAA 10:8). Данное письмо, датируемое до 671г. до н.э., на основе господствовавших в данный период астрологических представлений о мире и явлений в нём предопределяет будущее успешное завоевание главного геополитического противника Ассирии – Египта. Указывается, что понимание взаимосвязи движения планет и человеческой деятельности на психическом, а соответственно и физическом уровнях пронизывало всех ассирийских и вавилонских представителей той эпохи, а соответственно, придавало их уверенности дополнительную внутреннюю (эзотерическую) мотивировку. Подчёркивается, что сочетание всех указанных факторов (внутренняя мотивировка, психологическая, а затем и физическая подготовка) обеспечили в конечном итоге геополитическое преимущество ассирийской цивилизации над египетской в новоассирийский период. An attempt is made to show the political and military activities of the Assyrian king Esarhaddon in interaction with the analytical astrology on the example of the Letter to Ishtar-Shumu-Eresh - Esarhaddon (ABL 519 = LAS 13 = SAA 10:8). The transcription and translation of the most significant part of this letter is given, its style and professional language are analyzed. This letter, dated before 671. BC, on the basis of the astrological ideas about the world and phenomena prevailing in this period, determines the future successful conquest of the main geopolitical enemy of Assyria - Egypt. It is indicated that the understanding of the relationship between the movement of the planets and human activity at the mental, and, accordingly, physical levels, permeated all the Assyrian and Babylonian representatives of that era, and, accordingly, gave their confidence an additional internal (esoteric) motivation. It is emphasized that the combination of all these factors (internal motivation, psychological, and then physical training) ultimately ensured the geopolitical advantage of the Assyrian civilization over the Egyptian one in the Neo-Assyrian period.
Keywords: Филология